Transaminases and celiac disease: a relationship to be reassessed - Mennini, Maurizio; Ferrari, Federica; Valente, Michele; D'Amati, Giulia; Cucchiara, Salvatore (Progress in Nutrition, 2016)
Celiac Disease is a permanent intolerance to ingested gluten. The occurrence of liver impairment in CD is well described and can be regarded as one of the mainfold extra intestinal presentations of gluten-sensitive enteropathy. This increase is always mild or moderate, up to 5 times the upper limit of normal and transaminases decrease to normal range in most of patients on Gluten-free diet in maximum 12 months. We describe the case of a 16 months male addressed to our Operative Unit because of chronic diarrhea and poor weight growth with a severe increase of transaminases without a possible explanation. The case of our patient has highlighted the possibility of very high aminotransferase levels (up to 17 times the upper level normal of ALT) with a very slow decrease on a Gluten-free diet. It is necessary to study liver function in children at CD diagnosis and to seek celiac disease also in cases of severe hypertransaminasemia of unknown cause.